-4.9=-5.7+x

Simple and best practice solution for -4.9=-5.7+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4.9=-5.7+x equation:


Simplifying
-4.9 = -5.7 + x

Solving
-4.9 = -5.7 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-4.9 + -1x = -5.7 + x + -1x

Combine like terms: x + -1x = 0
-4.9 + -1x = -5.7 + 0
-4.9 + -1x = -5.7

Add '4.9' to each side of the equation.
-4.9 + 4.9 + -1x = -5.7 + 4.9

Combine like terms: -4.9 + 4.9 = 0.0
0.0 + -1x = -5.7 + 4.9
-1x = -5.7 + 4.9

Combine like terms: -5.7 + 4.9 = -0.8
-1x = -0.8

Divide each side by '-1'.
x = 0.8

Simplifying
x = 0.8

See similar equations:

| m+4=-6.7 | | 4.11x=16 | | 3c+12-c=78 | | 12-(-17)= | | 3(-2x+1)=21 | | -9-3x=-5x+7 | | x-9=6x+6 | | 0.9+0.3x=2.4 | | 4x+2=142 | | 2x-(3-x)=5+6x | | 2x^2=15-x | | 4x-(x+3)=15 | | 7=(-5-m)+4(6-m) | | -8+(-15)=(-15)+(-8) | | 15x=12(x-3) | | 5x+5+6x=5 | | -3m+4+5m=-6 | | 10x-9=-2x-69 | | 20x^3=50x | | 6(x-9)+x=7(x-9)+9 | | 3x+5=5(x-3) | | (2x+11y)(4x-9y)= | | 0=x^3-19x+18 | | 2x^2+15x=-7 | | 5(c+.80)+6=50 | | 2a+30=4a-4 | | 20+57x-9x^2=0 | | 7(2x-3)=7 | | 2x^2+30x+8=0 | | -4(2x-1)=6(x-2)-2 | | 8(3x+2)-18=-68 | | 7f+5=10(f-7)-3f |

Equations solver categories